Visuotactile apparent motion. - Harrar, V; Winter, R; Harris, L (2008)
This article compares the properties of apparent motion between a light and a touch with apparent motion between either two lights or two touches. Visual and tactile stimulators were attached to the tips of the two index fingers that were held apart at different distances. Subjects rated the quality of apparent motion between each stimulus combination for a range of stimulus onset asynchronies (SOAs). Subjects reported perceiving apparent motion between all three stimulus combinations. For light-light visual apparent motion, the preferred SOA and the direction threshold SOAs increased as the distance between the stimuli increased (consistent with Korte's third law of apparent motion). Touch-touch apparent motion also obeyed Korte's third law, but over a smaller range of distances, showing that proprioceptive information concerning the position of the fingers is integrated into the tactile motion system. The threshold and preferred SOAs for visuotactile apparent motion did not vary with distance, suggesting a different mechanism for multimodal apparent motion.